Ecological distribution patterns of Eremina desertorum in relation to Zygophyllum album, Thymelaea hirsuta, and climatic factors in its habitat in Egypt - Keshta, Amr E.; Ibrahim, Hesham; Bedair, Heba; Gad, Mohammed E.; Ghosh, Soumya; AL-Farga, Ammar; Ammar, Esraa El Saaed Ibrahim (Journal of Plant Protection Research, 2026)
This study examined the distribution of the desert snail Eremina desertorum (Forskål, 1775), a mollusk of economic importance, in arid desert environments. By exploring its ecological relationship with the plant species Thymelaea hirsuta (L.) Endl. and Zygophyllum album L.f. in Egypt, the research highlighted the correlation between these plants and the snail’s habitat preferences. Over the course of a year (from March 2021 to March 2022), 40 field visits were conducted across various locations along Egypt’s Mediterranean coast, encompassing all seasons. It was observed that E. desertorum tended to aggregate on T. hirsuta and Z. album, rather than on other wild plant species. Thus, the study aimed to predict the spatial distribution of E. desertorum by analyzing its relationship with these associated plants in Egypt, and the effect of prevailing climatic factors on its distribution, particularly seasonal precipitation and relative temperature. Spatial analyses over a decade (2012–2021) indicated that most E. desertorum populations were concentrated around the Nile and Upper Nile Deltaic regions, where Z. album was more prevalent than T. hirsuta. In contrast, T. hirsuta was predominantly recorded in the upper parts of Egypt, near the Mediterranean coast. Findings demonstrated a strong link between regions with higher precipitation and the presence of E. desertorum and its associated plants from the Zygophyllaceae (Z. album) and Thymelaeaceae (T. hirsuta) families. Furthermore, the snail showed a preference for plants known for higher water retention, which likely aids its survival in arid, water-scarce environments. These findings offer a useful framework for predicting the distribution of E. desertorum in relation to key plant associations and climatic conditions in arid environments. While the spatial data were based on previously recorded location coordinates, further studies focusing on population dynamics and broader plant comparisons could enrich the understanding of habitat preferences under shifting climate patterns.